Can circularity in Titanium metal improve EU strategic autonomy? Scenario modelling with heterogeneous data - Alejandro Buesa; Luis Pedauga; Pablo Pi\~nero; José Manuel Rueda-Cantuche; Brian Baldassarre (European Commission, 2024)
Strategic autonomy can be bolstered by applying circularity strategies such as reducing primary inputs and recycling critical raw materials in key technologies. However, effective actions require high definition at the material or technology level, leading to a non-systematic and often tedious data collection process. This paper extracts information from heterogeneous data sources attaining sufficient detail to conceive circularity scenarios and gauge their potential impact on global supply chains. Using titanium metal in the EU as a showcase, we start by merging qualitative, macroeconomic and micro-level trade information to disaggregate secondary (i.e., titanium scrap) flows depending on their production stage, sector of origin and quality. Subsequently, we design two enhanced circularity scenarios with marked strategic autonomy implications: a reduction of scrap buyback agreements in the EU with the US, and an increase in scrap collection from end-of-life aircraft. Finally, these scenarios are fed into an inter-country input-output model to compute their economic and employment impact. The results of our simulations show that the EU would benefit from valorising secondary titanium flows domestically, most notably if domestic processing capacity is also increased, by up to 20 million euros in value added and around 380 jobs.
Keywords: Q53; L61; D57; 330; Circular economy; open strategic autonomy; critical raw material; global value chains; titanium scrap; granular data; input-output